2012
DOI: 10.11111/jkana.2012.18.4.460
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Core Competencies Needed in the Fields of Nursing Practice for Graduates in Nursing

Abstract: Purpose: This study was done to provide information on issues of nursing core competencies needed in the fields of nursing practice for graduates in nursing, from the perspective of nursing managers, and to make suggestion for improving nursing education programs. Methods: Ten nursing managers participated in this study. They were in charge of clinical nursing education in the fields of nursing practice. Data were collected using focus group interviews and analyzed with the content analysis methodology of Down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…For this reason, nursing universities aim to not only equip nursing students with theoretical knowledge, skills, and attitudes necessary for nurses, but also get them to make quick adaptation to practical nursing sites and settle themselves in professional nursing positions [2]. However, new graduate nurses suffer diffi-culties while transitioning from student nurses to professional nurses, and decide to move workplaces or change jobs, which often lead them to drop out in the middle of their transitioning processes [3].…”
Section: Necessity Of Studymentioning
confidence: 99%
“…For this reason, nursing universities aim to not only equip nursing students with theoretical knowledge, skills, and attitudes necessary for nurses, but also get them to make quick adaptation to practical nursing sites and settle themselves in professional nursing positions [2]. However, new graduate nurses suffer diffi-culties while transitioning from student nurses to professional nurses, and decide to move workplaces or change jobs, which often lead them to drop out in the middle of their transitioning processes [3].…”
Section: Necessity Of Studymentioning
confidence: 99%
“…nursing curricula 15) . Consequently, the Korean Accreditation Board of Nursing has improved the quality of nursing education by continually revising education programs to produce students with the competencies demanded in domestic and international public healthcare.…”
Section: H7mentioning
confidence: 99%
“…Notably, new graduates were found to be inefficient or found to be needing verbal or physical assistance to integrate knowledge and skills in an emergency situation; almost 70 per cent of the new nurses felt incompetent to deal with an emergency situation in this study. Similar welldocumented findings in the contemporary literature show that responding to emergency situations is the biggest challenge in the first year of practice (Herron, 2018;Jang, 2009;Lee et al, 2012;Song, 2009;Thanomlikhit & Kheawwan, 2017). For example, Herron (2018) found that a lack of experience in an emergency situation was one of the factors that new graduates found challenging.…”
Section: Evidence-based Practice (Ebp) For New Graduate Nursesmentioning
confidence: 52%
“…Knowledge and skills were identified as the basic elements of evidence-based practice for new graduates in the present study. New graduates require theoretical nursing knowledge and basic nursing skills Ferguson & Day, 2007;Lee et al, 2012). However, this study found that only one-third of the nurse experts believed that new graduates possessed adequate theoretical nursing knowledge.…”
Section: Evidence-based Practice (Ebp) For New Graduate Nursesmentioning
confidence: 71%
See 1 more Smart Citation